2012
DOI: 10.1371/journal.pone.0036638
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the Treatment of Dry Eye: A Multicenter Randomised Controlled Trial with Active Comparison Intervention (Artificial Teardrops)

Abstract: PurposeTo evaluate the effects of acupuncture compared to a control group using artificial tears.Methods Setting & design: multicenter randomised controlled trial (three local research hospitals of South Korea). Study Population: 150 patients with moderate to severe dry eye. Intervention: Participants were randomly allocated into four weeks of acupuncture treatment (bilateral BL2, GB14, TE 23, Ex1, ST1, GB20, LI4, LI11 and single GV23) or to the artificial tears group (sodium carboxymethylcellulose). Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 38 publications
2
74
3
Order By: Relevance
“…According to recent studies, acupuncture may benefit midterm outcomes related to dry eye syndrome in comparison with artificial tears. 8 For example, acupuncture was found to improve the signs and symptoms of dry eye in patients after 4 weeks of treatment. 9 However, the effectiveness and mechanisms of acupuncture on postmenopausal dry eye have not yet been reported.…”
mentioning
confidence: 99%
“…According to recent studies, acupuncture may benefit midterm outcomes related to dry eye syndrome in comparison with artificial tears. 8 For example, acupuncture was found to improve the signs and symptoms of dry eye in patients after 4 weeks of treatment. 9 However, the effectiveness and mechanisms of acupuncture on postmenopausal dry eye have not yet been reported.…”
mentioning
confidence: 99%
“…14,16,18,19 Improvement in OSDI score during the study period is comparable to previous studies. 6,16,20 At 12 weeks, comparison was done between Group I and Group II. No intergroup difference was found between the groups with respect to Schirmer's and TBUT test, but signifi cant difference was found in OSDI score between the two study groups, this is in accordance with previous study 21 ( Figure 4).…”
Section: -11mentioning
confidence: 99%
“…The two new studies (published in 2012) that were added to the present analysis were the two largest, but they too suffered from a lack of double‐blinding. One of these studies found the observed effect decreased by the end of treatment, whereas the other found the effect was sustained until 8 weeks after treatment . Clearly, this difference leads to questions regarding the design of the studies.…”
Section: Commentarymentioning
confidence: 99%
“…One of these studies found the observed effect decreased by the end of treatment, 2 whereas the other found the effect was sustained until 8 weeks after treatment. 3 Clearly, this difference leads to questions regarding the design of the studies. However, this was not commented upon in the present analysis.…”
Section: Commentarymentioning
confidence: 99%